Pengaruh Fluktuasi Harga dan Luas Lahan Terhadap Pendapatan Petani Semangka di Desa Sumbersewu Kecamatan Muncar - Mauladana Hafiz Hakiki; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to examine and analyze the influence of price fluctuations and land area on the income of watermelon farmers in Sumbersewu Village, Muncar District, Banyuwangi Regency. The background of this research lies in the unstable income levels of watermelon farmers, primarily caused by fluctuating market prices and limited agricultural land ownership. These two factors are crucial since most of the population in Sumbersewu Village rely on watermelon farming as their main source of livelihood. The study adopts a quantitative approach with a causal research design. The population includes all watermelon farmers in the village, totaling 30 individuals, all of whom were used as the sample through a saturated sampling technique. Data were collected using a questionnaire that had undergone validity and reliability testing, and were analyzed using multiple linear regression with the aid of SPSS version 21. The results of this study show that: (1) there is a positive and significant influence of price fluctuations on farmers' income, (2) there is a positive and significant influence of land area on farmers' income, (3) there is a simultaneous significant influence between price fluctuations and land area on watermelon farmers' income. These findings imply that increasing farmers' income requires not only stable market prices but also strategic attention to technical aspects such as land access, productivity, and cost efficiency in agricultural practices.